[(Histamine)(18-crown-6)2][BF4]2 is a high-temperature piezoelectric. Issue 33 (6th April 2022) - Li, Yi-Rong; Zhang, Yun-Fang; Tang, Yuan-Yuan; Zhang, Han-Yue
Abstract : Host–guest inclusion [(histamine)(18-crown-6)2 ][BF4 ]2 shows decent piezoelectricity ( d 33 = 5 pC/N) and a high phase transition temperature of 406 K. Abstract : We discovered that [(histamine)(18-crown-6)2 ][BF4 ]2 is a high-temperature host–guest inclusion complex that presents decent piezoelectric properties ( d 33 = 5 pC/N), undergoes a phase transition at 406 K, and also possesses potential ferroelectricity. This work provides a new idea for constructing host–guest inclusion piezoelectrics.